2021
DOI: 10.12688/gatesopenres.13332.1
|View full text |Cite
|
Sign up to set email alerts
|

Pregnancy Surveillance Methods within Health and Demographic Surveillance Systems

Abstract: Background: Pregnancy identification and follow-up surveillance can enhance the reporting of pregnancy outcomes, including stillbirths and perinatal and early postnatal mortality. This paper reviews pregnancy surveillance methods used in Health and Demographic Surveillance Systems (HDSSs) in low- and middle-income countries. Methods: We searched articles containing information about pregnancy identification methods used in HDSSs published between January 2002 and October 2019 using PubMed and Google Scholar. A… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
2

Relationship

1
1

Authors

Journals

citations
Cited by 2 publications
(1 citation statement)
references
References 56 publications
(86 reference statements)
0
1
0
Order By: Relevance
“…Some HDSS sites register ongoing pregnancies to facilitate follow-up on pregnancy outcomes and early mortality [ 17 ]. We previously found that mortality during the first year of life was higher for cohorts of births with registered pregnancies compared to those where the pregnancy was not observed, implying omission of early deaths from the latter group [ 18 ].…”
Section: Introductionmentioning
confidence: 99%
“…Some HDSS sites register ongoing pregnancies to facilitate follow-up on pregnancy outcomes and early mortality [ 17 ]. We previously found that mortality during the first year of life was higher for cohorts of births with registered pregnancies compared to those where the pregnancy was not observed, implying omission of early deaths from the latter group [ 18 ].…”
Section: Introductionmentioning
confidence: 99%